"You Should Drink Less": Frequency and Predictors of Discussions Between Providers and Patients About Reducing Alcohol Use. (28th January 2017) - Farmer, Carrie M.; Stahlman, Shauna; Hepner, Kimberly A.
ABSTRACT: Background : Brief intervention is recommended for individuals who misuse alcohol, but studies vary on how frequently patients talk with their providers about alcohol use. Objectives : We examined whether veterans who had recently screened positive for alcohol misuse reported having conversations about their alcohol use with their providers. Methods : Following a positive screening for alcohol misuse during a primary care visit in 2013, veterans completed a telephone interview on alcohol use, conversations with their providers about drinking, and factors potentially associated with such conversations. The final analysis sample included 881 veterans; we conducted descriptive statistics and multivariable regression analyses. Results : Most veterans (83%) reported that their provider asked about drinking. Among these, 65% reported being advised to drink less, and 36% reported being advised to abstain. Veterans who received their healthcare from Veterans Health Administration (VA) had over twice the odds of reporting advice to reduce/abstain from drinking (adjusted odds ratio (AOR) = 2.34, 95% confidence interval (CI) = 1.46, 3.75). Veterans who reported heavy episodic drinking were more likely to report advice to reduce/abstain from drinking than those who did not report (AOR = 1.83, 95% CI = 1.30, 2.57) and veterans who reported heavy drinking were more likely to report such advice (AOR = 2.40, 95% CI = 1.69, 3.40). Conclusions / Importance : Most veterans with alcohol misuse reported receiving advice to reduce or abstain from drinking. Veterans with excessive alcohol use and those receiving all or most of their care from VA were more likely to report receiving such advice. Self-report of receiving advice may be an important approach to assessing appropriate follow-up after detection of alcohol misuse.